A culturally sensitive approach towards psychological health in Singapore : constructing and validating a taoist value questionnaire - Khoo, Athena Ming Gui (Nanyang Technological University, 2020)
The current mind-body model approach might not be sufficient in Asian societies whereby cultural philosophical beliefs are major influence of help-seeking behaviour and psychological health. Specifically, adopting the principles of Taoist values have been shown to be beneficial in alleviating symptoms of depression, anxiety, trait-anger and physical chronic illness. The current study aims to construct and examine the psychometrics properties of a Taoist Value Questionnaire (TVQ), a scale that measures one’s level of identification with Taoist values. Moderation analysis was also conducted to examine how one’s level of individualism, collectivism and relationalism moderates the relationship between Taoist values and psychological health. Four hundred and thirteen participants were recruited from Nanyang Technological University. Participants completed questionnaires pertaining to depression, anxiety, trait-anger, and psychological and physical health-related quality of life. Results from exploratory and confirmatory factor analysis indicated that a five-factor structure best represented the TVQ scale. The five TVQ domains were acceptance of law of nature, contentedness, noncompetition, limiting desires and dynamic revertism. Except for noncompetition, each of the TVQ domains were correlated with better psychological and physical health outcomes. Moderation analysis revealed individualism and relationalism moderated the relationship between Taoist values and psychological health while collectivism did not. These findings demonstrated the importance of a spirit-body-mind model towards psychological health. The TVQ can be a beneficial tool for future research that seeks to further assess the effects of Taoist values or to develop therapies that incorporate Taoist values.